1976
DOI: 10.1007/bf00033487
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of eyestalk removal in the crab Varuna litterata (Fabricius)

Abstract: Metabolic effects of eyestalk removal in the crab V. litterata is studied . Bilateral eyestalk ablation results in hypoglycaemia and a fall and rise in the glycogen content of hepatopancreas and muscle respectively . Injection of unboiled eyestalk extract evokes hyperglycaemia, whereas boiled eyestalk extract does not produce any significant change in the glycaemia level . The other effect of eyestalk removal is a fall in the fat content of the hepatopancreas and these results are discussed .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The 140% increase in the glycogen concentration in the digestive glands that took place 2 h after feeding could indicate the onset of glucogen synthesis (Tables I and IV). Hormones from the eyestalks could also be responsible for the metabolic control of the digestive gland in living animals (Silverthorn, 1975a, b;Kleinholz, 1976;Madyastha and Rangneker, 1976;Mauviot and Castell, 1976;Radakrishnan and Vijakumaran, 1984;Rosas et al, 1991). In fact, a 56% increase in oxygen consumption was recorded in the digestive gland of P. setiferus after 6 h (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The 140% increase in the glycogen concentration in the digestive glands that took place 2 h after feeding could indicate the onset of glucogen synthesis (Tables I and IV). Hormones from the eyestalks could also be responsible for the metabolic control of the digestive gland in living animals (Silverthorn, 1975a, b;Kleinholz, 1976;Madyastha and Rangneker, 1976;Mauviot and Castell, 1976;Radakrishnan and Vijakumaran, 1984;Rosas et al, 1991). In fact, a 56% increase in oxygen consumption was recorded in the digestive gland of P. setiferus after 6 h (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…The ablation of P. urgus lobster (Diaz-Iglesia et al, 1987) Vurunu fitterutu crab (Madhyastha and Rangneker, 1976) and H. umericunus lobster (Mauviot and Castell, 1976) eyestalks caused a decrease of glycogen and an increase of lipids in the hepatopancrease, muscle glycogen, oxygen consumption and growth of the animals. Sochasky et al (1973) andCaste11 et al (1976) also demonstrated that the nutritional status of the diet may play an important role in growth and survival of the ablated lobsters.…”
Section: Discussionmentioning
confidence: 99%
“…Freshly dissected meat was weighed and used for analyses. Protein, carbohydrate and lipid contents were analyzed adopting standard methods (Lowry et al, 1951;Dubois et al, 1956;Folch et al, 1957;Frings et al, 1972;Johnston and Davies, 1972).…”
Section: Methodsmentioning
confidence: 99%